2020
DOI: 10.1002/admt.201901152
|View full text |Cite
|
Sign up to set email alerts
|

Single Bimodular Sensor for Differentiated Detection of Multiple Oxidative Gases

Abstract: Semiconductive metal-oxide sensors suffer from cross-sensitivities under mixed chemical condition, specifically upon mixture of multiple oxidative or reducive gases. Herein, a single bimodular sensor has been demonstrated for smart differentation of multiple oxidative analytes by relating the resistance-metric mode to impedance-metric mode. The sensor construct based on ZnO nanorods readily outputs three response datasets upon exposure of oxidative-gas mixture including O 2 , SO 2 , and NO 2 , the resistance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…As a dimensionality reduction technique for machine learning (ML), principal component analysis (PCA) transforms high-dimensional data into a lower-dimensional representation, reducing the impact of errors, and improving recognition accuracy. After applying PCA, the data can be projected onto a 2D plane. , In Figure S7, the total variance explained by PC1 (65%) and PC2 (20%) is approximately 85%. Moreover, the key features selected during the dimensionality reduction process still retain a significant amount of the original information, facilitating a better understanding and interpretation of the data.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a dimensionality reduction technique for machine learning (ML), principal component analysis (PCA) transforms high-dimensional data into a lower-dimensional representation, reducing the impact of errors, and improving recognition accuracy. After applying PCA, the data can be projected onto a 2D plane. , In Figure S7, the total variance explained by PC1 (65%) and PC2 (20%) is approximately 85%. Moreover, the key features selected during the dimensionality reduction process still retain a significant amount of the original information, facilitating a better understanding and interpretation of the data.…”
Section: Results and Discussionmentioning
confidence: 99%
“…After applying PCA, the data can be projected onto a 2D plane. 45,46 In Figure S7, the total variance explained by PC1 (65%) and PC2 (20%) is approximately 85%. Moreover, the key features selected during the dimensionality reduction process still retain a significant amount of the original information, facilitating a better understanding and interpretation of the data.…”
Section: S T S ( )mentioning
confidence: 99%
“…In [203], Burgués et al utilized similar algorithms, a quadcopter, and two commercial SMO sensors to detect ethanol vapor sources in closed rooms and created a 3D map of gas concentration with a special resolution of 1.38 m. Notably, the measurements were conducted during continuous "sweeps" across the rooms, demonstrating the ability of the proposed algorithm to be utilized effectively and interpret data from relatively slow SMO sensors. The authors of [110] demonstrated the ability to effectively detect and distinguish between three different gases (O 2 , SO 2 , and NO 2 ) in a mixture with a single ZnO-based sensor. To achieve this functionality with an error of under 2%, resistance and impedance measurements were used, followed by data processing by an artificial neural network.…”
Section: Methods Of Processing Sensor Signals To Improve Sensitivity/...mentioning
confidence: 99%
“…18 To tackle these challenges, we demonstrated a single multimode sensor strategy in our previous work to enable direct measurement of the gas analyte mixture. 19 Such a multimodal sensor may integrate the merits of the traditional sensor array and single-mode sensor, where multifacet sensing signals in resistance and impedance response could be provided to evaluate the mixture on the basis of a simplified electrical feedthrough. It is noted that traditional sensor arrays integrate multiple devices or utilize massive data processing techniques 20 to achieve simultaneous recognition of different analytes and precise quantification.…”
mentioning
confidence: 99%
“…To tackle these challenges, we demonstrated a single multimode sensor strategy in our previous work to enable direct measurement of the gas analyte mixture . Such a multimodal sensor may integrate the merits of the traditional sensor array and single-mode sensor, where multifacet sensing signals in resistance and impedance response could be provided to evaluate the mixture on the basis of a simplified electrical feedthrough.…”
mentioning
confidence: 99%